Public investment project evaluation: case study on municipal solid waste sector in Portugal - Teixeira, C. (2016)
Over the past 20 years, the Portuguese State has held several public investments that have resulted in significant deviation in cost and deadlines and there is no record of benefits deviation, whose results, critical in terms of public spending, will contribute in a significant way to the burden of current and future generations. To be aware of the real dimension, financial deviation in relevant projects and public works (carried out either by direct administration of the State or in concession regime) in recent years have amounted to more than EUR 4.3 billion, i.e. about 2.5% of Portuguese GDP in 2014. This research work's core objective is responding to a commonly accepted gap among the Portuguese and which is related to the lack of practical assessment of the causes (ex-ante) and the respective impacts associated with large deviation in public investment projects, when compared to the initial estimates. Based on this diagnosis, which was itself based in four international benchmarks of good practices in project analysis/assessment and public audit, we intend to propose solutions that avoid repeating the same mistakes and failures in future cases (same-type study ones). For the purpose described above, the case study is the capital investment in Valorsul's Organic Recovery Centre (ORC), in the field sector of urban waste, which seeks to answer the following questions: How and why does Valorsul's ORC project present a high deviation? How could some of the deviation observed in the project have been prevented? How can the project contribute as a learning example for the Portuguese public investment area? The answer to these questions, which can be adapted to any type of project because the focus is on process management, shows that the factors that explain the reduced project performance are the adoption of non-validated assumptions, the absence of an analysis of sensitivity and risk, the degree of innovation of the project, non-existent or unreliable sources of information and insufficient qualification of the project analysis team. As for solutions to avoid repeating the same mistakes, one comes up with the urgent need for an entity that is able to previously assess and validate the goodness, the quality and the effective investment return for society and the actual need to implement a culture of sharing lessons learned. The methodology is similar to the "RG3" one, used in this research work, and such assessment and validation is performed in an independent manner. The question is whether these teachings will be discarded again and we continue to witness project management failures, with harmful effects on our economy and society.